Small-sized follicles could contribute to high-order multiple pregnancies: outcomes of 6552 intrauterine insemination cycles. Issue 5 (November 2018) - Giles, J; Cruz, M; González-Ravina, C; Caligara, C; Prados, N; Martínez, JC; Vergara, V; Requena, A
Abstract: Research question: Can predictors of twin and high-order multiple pregnancy among women with multiple cycles of ovarian stimulation intrauterine insemination (IUI) be identified? Design: Retrospective cohort study of IUI cycles carried out between January 2014 and December 2015 in a private clinic in Spain. The 4879 women and 6552 cycles analysed in this study include single IUI with ovarian stimulation using recombinant FSH. Results: Number of follicles and follicle size were the only factors with a significant effect ( P < 0.001) on the likelihood of achieving a twin or multifetal pregnancy. Follicles 12 mm or wider greatly increase the chances of achieving a twin or multifetal pregnancy. A total of 73 out of 127 (57.5%) twin pregnancies occurred in cycles with at least one additional follicle measuring 12 mm or wider, and 102 out of 127 twin pregnancies (80.3%) occurred in cycles with at least one additional follicle measuring 14 mm or wider. Cancellation criteria should consider the presence of follicles 12 mm or wider. Conclusion: Follicles measuring 12 mm or wider increase the risk of having a twin or a high-order multiple pregnancy rate. These data may help clinicians balance decision-making between cancelling and performing the cycle within an IUI procedure.